Effect of E-Service Quality, Brand Image and E-Security Seals on TOKOPEDIA E-Customer Satisfaction (Case Study on Tokopedia Customers) - Dimas Prawira; Rido Kurniawan; Richardus Eko Indrajit; Erick Dazki (Jurnal Informasi dan Teknologi, 2023)
This study aims to determine the effect of E-Security Service, E service quality and customer transaction security on TOKOPEDIA's Customer Satisfaction Level. The method used in this study is explanatory research (explanation) with a quantitative approach where the data source is primary and secondary data in the form of E-Commerce user data. Data were collected through questionnaires and analyzed using multiple linear regression with classical assumptions, namely the Normality Test, Multicollinearity Test, and Heteroscedasticity Test. Capital feasibility test is the coefficient of determination, F test and t test. Based on the results of the classic assumption test, it shows that E-Security Service, E service quality and customer transaction security simultaneously (together) have a significant effect on the dependent variable Tokopedia's Customer Satisfaction Level. Using a multiple regression analysis system, the results show that E-Security Service, E-service quality and customer transaction security have a partial effect on TOKOPEDIA's Customer Satisfaction Level with the E-Security Service variable value tcount 2.207 > ttable 1.675 and sig. the E-Security Service variable is 0.032 <0.05 meaning that there is a positive and significant influence between the E-Security Service variable on TOKOPEDIA's Customer Satisfaction Level, the value of the variable tcount E service quality tcount 6.897 > ttable 1.675 sig. the E-Security Service variable is 0.00 <0.05 meaning that there is a positive and significant effect between the E service quality variable on TOKOPEDIA's Customer Satisfaction Level, and the tcount E service quality variable value tcount 3.869 > ttable 1.675 sig. the E service quality variable is 0.00 <0.05 meaning that there is a positive and significant effect between the E service quality variable on TOKOPEDIA's Customer Satisfaction Level. Thus the better the E-Security Service, the E service quality and the existing customer transaction security, the higher the TOKOPEDIA Customer Satisfaction Level, conversely the worse the E-Security Service, E service quality and existing customer transaction security, the lower the Customer Satisfaction. TOKOPEDIA level